Biomass allocation and gas exchange are affected by light conditions in endangered Cedrela salvadorensis (Meliaceae) seedlings - Guzmán Q., J. Antonio; Cordero S., Roberto A.; Corea A., Eugenio (Revista de Biología Tropical, 2016)
The determination of favorable light habitat conditions per species and life stage is transcendental, for both ex situ and in situ conservation strategies of endangered forest tree species, and for their utilization as plantation trees. This becomes especially important when planting material is scarce. We studied the multivariate responses in biomass allocation and in gas exchange to light and to CO2 in Cedrela salvadorensis seedlings, grown under similar light conditions as those this species faces in nature. During a period of 135 days, groups of ten seedlings were put under 75, 45, 15 and 3.5 % of full sun exposure obtained with neutral shade cloth, under nursery conditions. A series of biomass allocation variables and detailed gas exchange parameters (photosynthesis response curves to light and to internal carbon concentration) were measured at the end of the growth period in plants of the four treatments. According to the principal component analyses, highest values of gas exchange response were associated with the lower values of biomass allocation traits. These changes can be associated with resource-conservative and resource-acquisitive strategies, where the C. salvadorensis seedlings acclimatize their traits for the exploration and exploitation of light, to high or to dim light environment, respectively. The multivariate analyses also showed that the plants had a high performance at 45 % of light environment. These results suggest that 45 % of light environment was the optimal light habitat of this species at the tested developing stage. Our results have important implications to choose the best natural habitat for a successful establishment of C. salvadorensis. We propose practical considerations for programs of reforestation or reintroduction where this species be involved.